Soil physical properties and crop productivity as affected by long-term conservation agriculture under maize (Zea mays) – wheat (Triticum aestivum)system in Indo Gangetic Plains - MANDAL, NANDITA; DAS, T K; MAITY, PRAGATI PRAMANIK (The Indian Journal of Agricultural Sciences, 2026)
Conservation agriculture (CA) incorporates crop management practices that can enhance productivity while conserving natural resources and improving soil physical properties. To assess this, an experiment was conducted during 2021–22 and 2022–23 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate soil physical properties and their impact on crop productivity in a long-term CA-based maize (Zea mays L.)–wheat (Triticum aestivum L.) system, initiated in 2010. The CA-based treatments were zero tillage with and without residue (ZT and ZT + R); permanent broad bed with and without residue (PBB and PBB + R); permanent narrow bed with and without residue (PNB and PNB + R) and conventional tillage (CT). The treatments were laid out under a randomised complete block design (RCBD) with three replications. Over the top 15 cm of soil, there was a 7.8% reduction in bulk density (BD) across the residue plots over non-residue plots. Although the highest porosity was observed in PNB + R (36.7%), all CA-based treatments were statistically comparable. Residue application had improved mean weight diameter (MWD) by 34.3% over CT, whereas a 22.6% increase in Ksat was reported in the study due to CA. At the plough layer, the highest soil organic carbon (SOC) was recorded under PBB + R (9.98 g/kg). A decreasing trend in soil properties (i.e. SOC, MWD and Ksat) was observed with increasing depth. Moreover, retaining residue in treatments PBB + R, ZT + R, and PNB + R caused a 13% rise in grain yield compared to treatments where residue was removed (PBB, ZT, PNB, CT). So, the outcomes of the experiment conclude that CA-based farming of maize– wheat cropping system could be practiced as a sustainable option to conserve soil and improve crop productivity in the long run.